STRATEGI PENINGKATAN KESELAMATAN TRANSPORTSASI UMUM DI DKI JAKARTA - Rahmoona, Iklima; Sulandari, Susi; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2015)
Public transportation safety is the latest issue that being attention because of the large number on traffic accident in DKI Jakarta who got involving public transportation in there. Traffic accident give disadvantage effect to the victims, a few causes of the traffic accident itself is the drivers of public transportation who drive under control, unworthy transportation public and facilities and infrastructure from public transportation that less on quality and quantity. This research method use qualitative and using the interview result from the seven informant in Dinas Perhubungan DKI Jakarta and Perhubungan Ministry. The interview results related to vision and mission, internal analysis, external analysis and SWOT analysis. After that, formulated the improving strategic based on the interview results and do litmust test to know the main priority from the improving strategic itself. The results showed the support and the blocked factors in the existing strategic of Dinas Perhubungan DKI Jakarta. The writer suggests to give the strategic improvement with improving the socialization and workshop program with invite the community related, optimalization the socialization and workshop program for individual owner of transportation public, additional in infrastructure and facility to give the people awareness about orderly traffic, budget optimalization to train the drivers safety of public transportation and the last is due and function optimalization in Dinas Perhubungan DKI Jakarta to train the drivers safety of public transportation.